The Effect Of Early Weight-Bearing On Lower Extremity Fracture Cases: A Narrative Review - Sri Sunaringsih Ika Wardojo; Salsabila Fernanda Djuliana; Rakhmad Rosadi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Background: One of disorder that causes limitations is fracture. Fractures will affect the patient's activities and quality of life. In surgery treated fracture commonly suggest to do non-weight-bearing and immobilization for 6 weeks. However, in several years there’s various study related to feasibility of early weight-bearing (EWB), EWB is performed by instructing the patient to apply load bearing according to the patient's tolerance. Research Methods: This study uses a narrative review method with the PICOS framework. The data search was obtain on the Pubmed and Google Scholar databases. The data used are international journals published in 2016-2022 that have through screening process. Research Results: The analysis outcome was 5 international journals that discuss the effectiveness of EWB. Based on these data, it shows that there is effect in the form of feasibility and minimal complications. Conclusion: The analysis based on the data obtained show that there was effect of EWB on lower extremity fracture.